Reactive extrusion process to obtain a multifunctional fiber-rich ingredient from coffee hull - Jessika Soares Jacinto; Janaina Mantovan; Jaquellyne Bittencourt Moraes Duarte da Silva; Suzana Mali de Oliveira (Revista Principia)
Brazil, known for its robust agricultural sector, generates substantial amounts of lignocellulosic residues annually. The valorization of these residues as ingredients for the food industry aligns with environmental, social, and economic sustainability goals. Coffee hull, a by-product of the coffee industry, holds potential as a source for creating high-value food ingredients. This study aimed to develop a multifunctional, fiber-rich ingredient from the coffee hull using a one-step reactive extrusion process with either alkaline hydrogen peroxide or sulfuric acid. The coffee hull was subjected to extrusion with sulfuric acid (1% and 3%) or alkaline hydrogen peroxide (1% and 3%) in these one-step processes. The resulting materials were then analyzed for their physicochemical and techno-functional properties. All treated samples demonstrated an increased cellulose and insoluble dietary fiber content, along with enhanced porosity, as observed through scanning electron microscopy. The sample treated with 3% alkaline hydrogen peroxide (AHP3) exhibited the highest levels of cellulose (45.17%), insoluble dietary fiber (78.20%), density (3.54), water absorption capacity (1.96 g/g), and oil absorption capacity (0.86 g/g). Furthermore, all samples displayed thermal stability from room temperature up to 300 °C, and a reduction in crystallinity indexes was noted after treatment. The reactive extrusion method proved effective in modifying the coffee hull, offering a green approach to producing high-value products from lignocellulosic waste. This method presents several advantages, including short reaction times, low reagent concentrations, minimal or no effluent generation, and potential scalability for industrial scale.